RANCANG BANGUN MESIN IMPAK CHARPY DAN KESAN PERTAMANYA TEHADAP MINAT BELAJAR MAHASISWA PADA MATAKULIAH ILMU BAHAN - Munib Rosadi, Mohammad; Basuki; Samudra, Agung; Hasbi Ramadani, Ali (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
The need for measuring the mechanical properties of material in the Material Science course makes thecharpy impact machine to be immediately presented to be a supporting tool as well as a reference forstudents in carrying out impact testing. The purpose of this study was to find out how to design and createa charpy impact machine, find out how to work and analyze performance based on the impact energyreceived by the specimen and find out the impact on student learning interest in the Materials Sciencecourse. This research is a design research that ultimately produces a product. The performance of the tooluses ten steel specimens with dimensions of 10mm x 10 mm x 55 mm indicating an average impact priceof 1,509601 J / mm2. The measurement results of the learning interest questionnaire showed an indicatorof student interest in the presence of the charpy impact testing machine in the materials science course at73.68%..Keywords: design, impact, charpy, learning interest